Fatigue bond strength of dental adhesive systems: Historical background of test methodology, clinical considerations and future perspectives - Akimasa Tsujimoto; Wayne W. Barkmeier; Erica C. Teixeira; Toshiki Takamizawa; Masashi Miyazaki; Mark A. Latta (Elsevier, 2022)
Numerous laboratory evaluations have been conducted since Dr. Rafael Bowen introduced a method for determining the bond strengths of adhesive systems to dental substrates in 1965. Most of the past studies have been conducted using static bond strength tests, such as shear and tensile bond strength testing with either macro or micro sized specimens. These static bond strength tests are conducted using a monotonically increasing load in which stress is applied continuously until failure occurs. Although the type of stress that develops in static bond strength tests is not typically encountered in clinical situations, over the years clinicians have based their choice of adhesive systems for use in daily practice on the results of such tests. However, some well-known researchers have reported that the results obtained from static bond strength testing may have limited clinical relevance and should not be used only by themselves to make recommendations for clinical use. In clinical situations, restorations undergo cyclic stress during mastication at stress levels well below the breaking stress used in static bond strength tests. Thus, dynamic bond strength tests, using cyclic loading, should be more clinically relevant than static bond strength tests. Over 15 years, a testing method designed to assess fatigue bond strengths of dental adhesive systems has been developed through inter-collegial and international collaborative efforts. This review discusses the development of fatigue bond strength testing methodology, provides both a historical perspective and current information regarding available testing data for all categories of adhesive systems to enamel and dentin and perspectives on the future development of both adhesive systems and testing methods.